Biogeochemical layering and transformation of particulate organic carbon in the Tropical Northwestern Pacific Ocean inferred from δ13C - D. Tian; D. Tian; X. Li; X. Li; X. Li; X. Li; J. Song; J. Song; J. Song; J. Song; J. Ma; J. Ma; et al. (Ocean Science, 2025)
Particulate organic carbon (POC) serves as the main carrier of the biological pump and determines its transmission efficiency, yet the transformation processes of POC remain incompletely understood. This study reports the vertical distribution of POC, dissolved inorganic carbon (DIC), δ13C-POC, and δ13C-DIC in the tropical Northwestern Pacific Ocean (TNPO). The research identified three distinct biogeochemical layers governing POC transformation: the POC rapid synthesis-degradation layer (RSDL, 0–300 m), the net degradation layer (NDL, 300–1000 m), and the stable layer (SL, 1000–2000 m). From the top to the bottom of the RSDL, δ13C-POC values decreased by an average of 2.23 ‰, while the carbon-to-nitrogen (C:N) ratios increased by an average of 2.3:1, indicating the selective degradation of POC. In the NDL, δ13C-POC and δ13C-DIC exhibited a significant negative correlation (r=0.43, p<0.05), indicating a net transformation of POC to DIC. In the SL, POC proved to be resistant to degradation, with POC exhibiting the highest C:N (15:1 on average) and the lowest δ13C-POC values (average −27.71 ‰).